2017
DOI: 10.1021/acs.estlett.7b00081
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Neonicotinoid Insecticides in Finished Drinking Water and Fate during Drinking Water Treatment

Abstract: Neonicotinoid insecticides are widespread in surface waters across the agriculturally intensive Midwestern United States. We report for the first time the presence of three neonicotinoids in finished drinking water and demonstrate their general persistence during conventional water treatment. Periodic tap water grab samples were collected at the University of Iowa over 7 weeks in 2016 (May–July) after maize/soy planting. Clothianidin, imidacloprid, and thiamethoxam were ubiquitously detected in finished water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(159 citation statements)
references
References 32 publications
10
147
2
Order By: Relevance
“…Karmakar et al () observed significantly larger k obs for thiamethoxam in phosphate‐buffered solutions at pH 4.0 (100 times larger) and pH 7.0 (10 times larger) than was observed in the present study. Klarich et al (), however, saw no hydrolysis at pH 7, consistent with the present results.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Karmakar et al () observed significantly larger k obs for thiamethoxam in phosphate‐buffered solutions at pH 4.0 (100 times larger) and pH 7.0 (10 times larger) than was observed in the present study. Klarich et al (), however, saw no hydrolysis at pH 7, consistent with the present results.…”
Section: Resultssupporting
confidence: 93%
“…Baseline imidacloprid results are similar to previously reported hydrolysis studies, in which imidacloprid was only observed to react at pH values >9 (Zheng and Liu ; Liu et al ). Thiamethoxam hydrolysis kinetics at high pH were similar to previously reported work (Liqing et al ; Karmakar et al ; Klarich et al ). Karmakar et al () observed significantly larger k obs for thiamethoxam in phosphate‐buffered solutions at pH 4.0 (100 times larger) and pH 7.0 (10 times larger) than was observed in the present study.…”
Section: Resultssupporting
confidence: 90%
“…The presence of neonicotinoids has been detected in various types of water reservoirs, including ditches, pools, ponds, mountain streams, rivers, periodic marshes, meltwater, and groundwater, effluents from WWTPs, and drinking water . The monitoring data were mainly available for four or less EU countries although neonicotinoids are widely used in Europe as Plant Protection Products (PPPs) and biocides.…”
Section: Occurrence Of Pesticides In Water In the Eu And Worldwidementioning
confidence: 99%
“…(Kearns et al, 2016). Common insecticides used in urban and agricultural areas have been detected in drinking water and in 40% of sampled streams in the Midwest, the latter at levels that caused harm to artificial aquatic ecosystems (Klarich et al, 2017;Rogers et al, 2016).…”
Section: Appendix A: Waste Impacts On Natural Resources and Human Welmentioning
confidence: 99%